Perinatal Western-style diet alters serotonergic neurons in the macaque raphe nuclei - Dunn, Geoffrey A.; Thompson, Jacqueline R.; Mitchell, A J; Papadakis, Samantha; Selby, Matthew; Fair, Damien; Gustafsson, Hanna C.; Sullivan, Elinor L. (Frontiers in Neuroscience, 2023)
Introduction The neurotransmitter serotonin is a key regulator of neurotransmission, mood, and behavior and is essential in neurodevelopment. Dysfunction in this important neurotransmitter system is connected to behavioral disorders such as depression and anxiety. We have previously shown that the developing serotonin system is sensitive to perinatal exposure to Western-style diet (WSD). Methods To advance our hypothesis that perinatal WSD has a long-term impact on the serotonergic system, we designed a fluorescent immunohistochemistry experiment using antibodies against tryptophan hydroxylase 2 (TPH2) and vesicular glutamate transporter 3 (VGLUT3) to probe protein expression in the raphe subnuclei in 13-month-old Japanese macaques (Macaca fuscata; n = 22). VGLUT3 has been shown to be coexpressed in TPH2+ cells in the dorsal raphe (DR) and median raphe nucleus (MnR) of rodent raphe nuclei and may provide information about the projection site of serotonergic fibers into the forebrain. We also sought to improve scientific understanding of the heterogeneity of the serotonin production center for the central nervous system, the midbrain raphe nuclei. Results In this immunohistochemical study, we provide the most detailed characterization of the developing primate raphe to date. We utilize multi-level modeling (MLM) to simultaneously probe the contribution of WSD, offspring sex, and raphe anatomical location, to raphe neuronal measurements. Our molecular and morphological characterization revealed that the 13-month-old macaque DR is remarkably similar to that of adult macaques and humans. We demonstrate that vesicular glutamate transporter 3 (VGLUT3), which rodent studies have recently shown can distinguish raphe populations with distinct projection targets and behavioral functions, likewise contributes to the heterogeneity of the primate raphe. Discussion This study provides evidence that perinatal WSD has a long-term impact on the density of serotonin-producing neurons, potentially limiting serotonin availability throughout the brain. Due to the critical involvement of serotonin in development and behavior, these findings provide important insight into the mechanisms by which maternal nutrition and metabolic state influence offspring behavioral outcomes. Finally, these findings could inform future research focused on designing therapeutic interventions to optimize neural development and decrease a child’s risk of developing a mental health disorder.